IPAS learning innovation through powtoon based animation video in grade IV elementary school - zanuba arriffah chafsoh (Jurnal Gentala Pendidikan Dasar, 2025)
This research aims to develop animated video learning media using Powtoon on the subject of IPAS for fourth-grade elementary school students. The background of this study is the lack of effective and engaging media used in IPAS learning, which still relies on static visual aids that do not suit the learning characteristics of students in the concrete operational stage. The research method used is R&D with the ADDIE. Data were obtained through expert validation, teacher and student response questionnaires, and learning outcome tests (pretest and posttest). The media was validated by three experts: a media expert (86%), a content expert (96%), and a language expert (86.67%), all categorized as very valid. Practicality test results showed 94% from the teacher and 96.3% from students, categorized as very practical. Effectiveness was measured using learning outcome tests, which showed an increase in average scores from 76 (pretest) to 94.5 (posttest), with a mastery learning percentage of 81.4%, categorized as very effective. Thus, Powtoon-based animated video is considered valid, practical, and effective as a learning innovation in the IPAS subject for fourth-grade elementary school students.